Duźe zwierzę . Big Animal - Stuhr, Jerzy (Rogowski, Slawomir, 2000)
Duration: 01:13:00 The screenplay for this film was originally written by Krzysztof Kieślowski and was supposed to be his debut. Sawicki - a respected citizen of small mountain town – one day starts walking around with a camel left there by a circus crew. The community is shocked. The authorities demand that the animal be registered and taxed. They start receiving anonymous letters saying that the animal distracts children at school, fouls the streets and – worst of all – could be carrying some special kind of African venereal disease. Sawicki and his wife are slowly excluded from the community. Others, such as a local photographer or the TV station, want to make money out of the animal. Sawicki resists all these pressures but feels increasingly trapped. A tongue-in-cheek, but ultimately sad film about the fear of the “Other”.